2015
DOI: 10.12678/1089-313x.19.1.22
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Manipulated and Accurate Assessment Feedback on the Self-Efficacy of Dance Students

Abstract: Research undertaken with athletes has shown that lower-evaluated feedback is related to low self-efficacy levels. However, the relationship between teacher feedback and self-efficacy has not been studied in the dance setting. In sports or dance contexts, very few studies have manipulated feedback content to examine its impact on performers' self-efficacy in relation to the execution of a specific movement. Therefore, the aim of this investigation was to explore the effect of manipulated upper, lower, and accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Similar to our findings, several researchers have elucidated the effects of dance on ROM in various disorders 3,10–13,17,20,22,32,35,36,38,4245. Dance involves intentional movements, which supports the findings of our study that it increases ROM of lower limbs, as well as its influence on the movements of head, trunk, and upper limbs were also studied.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to our findings, several researchers have elucidated the effects of dance on ROM in various disorders 3,10–13,17,20,22,32,35,36,38,4245. Dance involves intentional movements, which supports the findings of our study that it increases ROM of lower limbs, as well as its influence on the movements of head, trunk, and upper limbs were also studied.…”
Section: Discussionsupporting
confidence: 92%
“…Movements were assessed bilaterally in the frontal, sagittal, and transversal planes. Hip joint: flexion (flexion of hip with knee in flexion and extension), extension, abduction, adduction, and external and internal rotation; knee joint: flexion and extension movements; ankle joint: dorsal flexion, plantar flexion, abduction, adduction, inversion, and eversion 5,12,22…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the more accurate quantified data in feedback are provided, the better the learning effects for [41]. Some studies also reported that students' self-efficacy is likely to increase when feedback is accurate [42]. Based on these findings, the data we measured can be used as feedback for enhancing motor control in basic AM.…”
Section: Discussionmentioning
confidence: 69%
“…Garcia-Dantas and Quested (2015) identified that when students receive objective and accurate feedback instead of just a general score (such as a ranking), then they can focus future efforts on what they need to change about their performance to succeed. Objective feedback holds the dancer accountable and can empower a dancer to improve her performance.…”
mentioning
confidence: 99%